2022
DOI: 10.1111/jspn.12368
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of parent's knowledge of hospital‐based pediatric falls

Abstract: Purpose: This study aimed to validate and to determine the individual characteristics and demographic factors associated with parents' knowledge of hospital-based pediatric falls and to identify parent populations more likely to report low levels of falls-related knowledge. Design: Validation of a questionnaire and a cross-sectional survey design. Methods: Parents (n = 200) of hospitalized children admitted to a tertiary specialist pediatric hospital in Australia completed an online questionnaire. Parents were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Because most parent were present in fall events of child, parent presence is not protective against the falls of their children in hospital [ 20 , 21 ]. Actually, the parents’ knowledge that children may fall during parental presence rated the lowest score in Australia [ 22 ]. This emphasizes the importance of evaluating whether parents have accurate knowledge and perception of child falls and educating them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because most parent were present in fall events of child, parent presence is not protective against the falls of their children in hospital [ 20 , 21 ]. Actually, the parents’ knowledge that children may fall during parental presence rated the lowest score in Australia [ 22 ]. This emphasizes the importance of evaluating whether parents have accurate knowledge and perception of child falls and educating them.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that there is a possibility that falls may occur as the hospitalization date passes, along with the consequences of falling even though the caregiver resides. This can be attributed to the caregivers’ complacency according to the familiarity of the hospital environment and lack of awareness of the risk of falls [ 22 , 23 ]. Therefore, fall prevention education for hospitalized children should not be limited to the early stages of hospitalization but should continue throughout hospitalization, and continuous education and observation are required to ensure the awareness and attention of caregivers concerning fall events [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the risk factors for falls in hospitalized children are multifaceted (AlSowailmi et al, 2018;Parker et al, 2020;Kim & Lee, 2021) and comprehensive multifaceted intervention measures should be taken (Liu & Shang, 2021;Sheppard-Law et al, 2022). At present, the nursing measures to prevent falls in hospitalized children mainly include fall risk assessment, using the high-risk sign/sticker, close observation, assistance during children′s ambulation, family and staff education, composition of a safe environment and never leaving the child alone .…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…A fall is “a sudden, unintentional descent, with or without injury to the patient that results in the patient coming to rest on the floor, on or against some other surface, on another person, or an object” (National Database of Nursing Quality Indicators (NDNQI), 2020). Studies have shown that the risk factors for falls in hospitalized children are multifaceted (AlSowailmi et al, 2018; Parker et al, 2020; Kim & Lee, 2021) and comprehensive multifaceted intervention measures should be taken (Liu & Shang, 2021; Sheppard‐Law et al, 2022). At present, the nursing measures to prevent falls in hospitalized children mainly include fall risk assessment, using the high‐risk sign/sticker, close observation, assistance during children′s ambulation, family and staff education, composition of a safe environment and never leaving the child alone (Kim, Kim, & Lim, 2021).…”
Section: Introductionmentioning
confidence: 99%